Induction of Phenylalanine Ammonia-lyase in Xanthium Leaf Disks. Photosynthetic Requirement and Effect of Daylength - Zucker, Milton (1969)
A cycloheximide-sensitive increase in the activity of phenylalanine ammonia-lyase (EC 4.3.1.5) occurs in Xanthium leaf disks exposed to light. Radioactive ammonia-lyase has been isolated by means of sucrose density gradient centrifugation and starch gel electrophoresis from disks fed l-isoleucine-U-(14)C or l-arginine-U-(14)C. The incorporation of radioactive amino acids into phenylalanine ammonia-lyase together with the inhibitory effects of cycloheximide indicate that the observed increase in enzyme activity involves the induction of lyase synthesis. The light-dependent synthesis of the ammonia-lyase is completely inhibited by 50 μm 3-(4-chlorophenyl)-1,1-dimethylurea (CMU) indicating that photosynthesis is involved. Only a trace quantity of some photosynthetic product must be needed because half light saturation occurs at very low intensity (ca. 30 ft-c). Exogenous carbohydrate is also required for continuing enzyme synthesis over a 72 hr period. But carbohydrate does not replace the photosynthetic requirement in darkness. Enzyme formed in light disappears rapidly from disks placed in the dark. The decay of ammonia-lyase activity follows first order kinetics. The half-life of the lyase ranged from 6 to 15 hr in leaf material used. Cyoloheximide inhibits the decay of lyase activity. Thus the maintenance of turnover in Xanthium leaf disks requires de novo synthesis of protein. That turnover, i.e., degradation as well as synthesis of lyase protein occurs is suggested by the apparent loss of radioactive ammonia-lyase from leaf disks placed in darkness. Light-induced synthesis coupled with rapid turnover can produce a diurnal fluctuation of ammonia-lyase activity in Xanthium leaf disks. Alternating periods of enzyme synthesis and degradation were observed in disks exposed to 24 hr cycles of light and dark. The average level of enzyme activity maintained in the tissue was directly related to the length of the light period. Induction of lyase synthesis was also observed in excised leaves and to a lesser extent in leaves of whole plants.